Kegagalan pemaknaan “Lembaga Musawarah Perencanaan dan Pembangunan Desa”dalam mewujudkan deepening democracy - Novita Tresiana; Noverman Duadji (Masyarakat, Kebudayaan dan Politik, 2016)
Government’s failure in the provision of public goods and ideas deepening democracy were considered as a panacea for the success of rural development. The objective of this research is to describe the village development planning in achieving policy production and to find essential elements in attempt to realize a superior deliberative policy. This research uses qualitative method. Research conducted in Southern Lampung, the Province of Lampung. Initial description obtained by understanding the meaning of emic and cross-subject inverstigation by comparing concept (theory), interpretation, and deliberative substantive policy theory formulation. Informant for this research consist of head of village and village officers, subdistrict head and its staff, SKPD in Southern Lampung Regency and chief and officers of provincial assembly; (2) elit and political party figures, Non-governmental organization and choosen villagers; (3) businessmen and local group interest and (4) academician. Data gathered through: 1) Observation; (2) In-depth interview; (3) Document; and 4) Focus Group Discussion (FGD). Data analyzedd by Miles and Huberman interactive analysis. This paper reveals that the village development planning was seen as a goal, when it was just a selected tool or process. Essential elements required to achieve public policy excellence: by strengthening the institutional capacity of the government through new dialogue space and community engagement through deliberative forum. It requires commitment, active community involvement, citizens’ trust, and social networks.